Panchatantra: illustrated tales from ancient India - Sharma's, Pandit Vishnu (Noida : Wonder House, 2022)
The stories his own energy and insights, and the stories are brought to life by Ishan$1 (Bs marvellous illustrations. Every moral lesson at the end of every chapter is a practical guide for life for children and adults alike.s